Silver nanoparticle based surface-enhanced Raman spectroscopy for label-free discrimination of diabetic albumin under near-infrared laser excitation. (24th July 2018) - Lin, Jinyong; Lin, Xueliang; Hu, Cairong; Bai, Penggang; Yang, Haisong; Dai, Yitao; Qiu, Hejin; Lin, Ming; Feng, Shangyuan; Pan, Jianji; Chen, Rong; Lin, Juqiang; et al.
Abstract: Albumin glycation is an important marker for detecting type II diabetes. In the present study, a label-free blood albumin analysis based on laser surface-enhanced Raman spectroscopy for diabetes screening is presented. Membrane electrophoresis (ME) was applied to human plasma samples to first purify the albumin and then silver nanoparticles were added to stimulate surface-enhanced Raman scattering (SERS) signals. Subtle but discernible differences in the normalized average spectra between the diabetic ( n   =  35) and healthy ( n   =  45) groups were acquired. SERS band assignments suggested that glycation resulted in structural changes of albumin in diabetes. Principal component analysis and linear discriminant analysis were used to further analyze the subtle glycation features and discriminate the diabetic SERS spectra from the normal ones with high specificity of 100%. This exploratory study shows that surface-enhanced Raman spectroscopy in combination with ME can be a clinically useful tool for label-free detection of albumin glycation and ultimately type II diabetes screening.